Sir Cumference and the Sword in the Cone : A Math Adventure - Cindy Neuschwander (Watertown, United States Charlesbridge Publishing,U.S., 2003)
King Arthur has issued a challenge. The first knight to find the sword Edgecalibur will be the next king. Join Sir Cumference, Lady Di of Ameter, and their son, Radius, as they race to help their friend, Vertex, find the sword and discover the secrets of cubes, pyramids, cylinders, and cones.